Training in Creating Educational Videos for Teachers of State Senior High School 3 Tidore Islands: Pelatihan Pembuatan Video Pembelajaran untuk Guru SMA Negeri 3 Tidore Kepulauan - Syarifuddin N. Kapita; Rosihan; Arifandy Mario Mamonto (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
The community engagement activity took place in Gamtufkange Village, Tidore City, Tidore District, North Maluku Province, with the activity focus on State Senior High School 3 Tidore Islands. This activity provided training on how to create instructional videos using Edpuzzle, synchronized with Google Classroom. The training aimed to enhance the understanding and skills of the teachers at State Senior High School 3 in utilizing Edpuzzle and Google Classroom as effective tools for creating and using educational videos. The resulting works were then utilized by the teachers of State Senior High School 3 Tidore Islands in the teaching and learning process